Variation in global uptake of the Surgical Safety Checklist. Issue 2 (5th January 2020) - Delisle, M; Pradarelli, J C; Panda, N; Koritsanszky, L; Sonnay, Y; Lipsitz, S; Pearse, R; Harrison, E M; Biccard, B; Weiser, T G; Haynes, A B
Abstract: Background: The Surgical Safety Checklist (SSC) is a patient safety tool shown to reduce mortality and to improve teamwork and adherence with perioperative safety practices. The results of the original pilot work were published 10 years ago. This study aimed to determine the contemporary prevalence and predictors of SSC use globally. Methods: Pooled data from the GlobalSurg and Surgical Outcomes studies were analysed to describe SSC use in 2014–2016. The primary exposure was the Human Development Index (HDI) of the reporting country, and the primary outcome was reported SSC use. A generalized estimating equation, clustering by facility, was used to determine differences in SSC use by patient, facility and national characteristics. Results: A total of 85 957 patients from 1464 facilities in 94 countries were included. On average, facilities used the SSC in 75·4 per cent of operations. Compared with very high HDI, SSC use was less in low HDI countries (odds ratio (OR) 0·08, 95 per cent c.i. 0·05 to 0·12). The SSC was used less in urgent compared with elective operations in low HDI countries (OR 0·68, 0·53 to 0·86), but used equally for urgent and elective operations in very high HDI countries (OR 0·96, 0·87 to 1·06). SSC use was lower for obstetrics and gynaecology versus abdominal surgery (OR 0·91, 0·85 to 0·98) and where the common or official language was not one of the WHO official languages (OR 0·30, 0·23 to 0·39). Conclusion: Worldwide, SSC use is generally high, but significant variability exists. Implementation and dissemination strategies must be developed to address this variability. Graphical Abstract: The Surgical Safety Checklist (SSC) is a patient safety tool shown to reduce mortality and improve teamwork and adherence with perioperative safety practices. Since its introduction a decade ago, the global uptake of the SSC has been generally high, but significant variability exists. Implementation and dissemination strategies must be developed to address this variability. Variable implementation A video abstract is available at https://youtu.be/ihlppbeU_9s